3D printing of liquid metals as fugitive inks for fabrication of 3D microfluidic channels. Issue 10 (30th March 2016) - Parekh, Dishit P.; Ladd, Collin; Panich, Lazar; Moussa, Khalil; Dickey, Michael D.
Abstract : This paper demonstrates a simple method to fabricate 3D microchannels at room temperature by printing liquid metal as a sacrificial template. Abstract : This paper demonstrates a simple method to fabricate 3D microchannels and microvasculature at room temperature by direct-writing liquid metal as a sacrificial template. The formation of a surface oxide skin on the low-viscosity liquid metal stabilizes the shape of the printed metal for planar and out-of-plane structures. The printed structures can be embedded in a variety of soft ( e.g. elastomeric) and rigid ( e.g. thermoset) polymers. Both acid and electrochemical reduction are capable of removing the oxide skin that forms on the metal, which destabilizes the ink so that it withdraws from the encapsulating material due to capillary forces, resulting in nearly full recovery of the fugitive ink at room temperature. Whereas conventional fabrication procedures typically confine microchannels to 2D planes, the geometry of the printed microchannels can be varied from a simple 2D network to complex 3D architectures without using lithography. The method produces robust monolithic structures without the need for any bonding or assembling techniques that often limit the materials of construction of conventional microchannels. Removing select portions of the metal leaves behind 3D metal features that can be used as antennas, interconnects, or electrodes for interfacing with lab-on-a-chip devices. This paper describes the capabilities and limitations of this simple process.